The Behavioral Foundations of Public Policy - Shafir, Eldar (Princeton University Press, 2013)
In recent years, remarkable progress has been made in behavioral research on a wide variety of topics, from behavioral finance, labor contracts, philanthropy, and the analysis of savings and poverty, to eyewitness identification and sentencing decisions, racism, sexism, health behaviors, and voting. Research findings have often been strikingly counterintuitive, with serious implications for public policymaking. In this book, leading experts in psychology, decision research, policy analysis, economics, political science, law, medicine, and philosophy explore major trends, principles, and general insights about human behavior in policy-relevant settings. Their work provides a deeper understanding of the many drivers--cognitive, social, perceptual, motivational, and emotional--that guide behaviors in everyday settings. They give depth and insight into the methods of behavioral research, and highlight how this knowledge might influence the implementation of public policy for the improvement of society. This collection examines the policy relevance of behavioral science to our social and political lives, to issues ranging from health, environment, and nutrition, to dispute resolution, implicit racism, and false convictions. The book illuminates the relationship between behavioral findings and economic analyses, and calls attention to what policymakers might learn from this vast body of groundbreaking work. Wide-ranging investigation into people's motivations, abilities, attitudes, and perceptions finds that they differ in profound ways from what is typically assumed. The result is that public policy acquires even greater significance, since rather than merely facilitating the conduct of human affairs, policy actually shapes their trajectory. The first interdisciplinary look at behaviorally informed policymaking Leading behavioral experts across the social sciences consider important policy problems A compendium of behavioral findings and their application to relevant policy domains.- Resumé vydavatel